Dose-response effects of exercise on behavioral health in children and adolescents. (March 2017) - Bowling, April; Slavet, James; Miller, Daniel P.; Haneuse, Sebastien; Beardslee, William; Davison, Kirsten
Abstract: Purpose: Aerobic exercise may positively affect behavior in children but little research has been conducted among those with behavioral health disorders (BHD). This study is a secondary exploration of data originally collected from an RCT that tested effects of a cybercycling intervention on behavior in children with BHD. We examine dose-response relationships between duration and intensity of cybercycling and minutes of disciplinary time spent out of class (TOC) and self-regulation scores (SRS); additionally we examine potential effect modification by Attention-Deficit/Hyperactivity Disorder (ADHD) diagnosis. Methods: We extracted data from study days on which participants (N = 103, 83.5% male, age 11.8 ± 2.3) cybercycled during physical education classes. Minutes of riding and average heart rate for each session were collected via the bicycles. The Conners Abbreviated Teacher Rating Scale (SRS) and minutes of TOC were recorded daily. Ride duration and average heart rate were treated as continuous predictors of outcomes using mixed-effects linear regression. Results: For every 10 min of riding, children had an associated decline of 10.7 min of TOC (p < 0.001) and 1.2 points improvement in self-regulation score (p = 0.001). For each increase of 10 beats per minute average heart rate children had an associated decline of 1.3 min (p = 0.05) and 0.21 points (p < 0.05). Children with ADHD experienced 12.9 min less time out of class (p < 0.05) for each 10 additional minutes of riding. Conclusion: Duration in particular had significant, linear relationships with improved behavioral outcomes among children with a variety of BHD; children with ADHD may experience the greatest benefits. Highlights: Exercise-behavior dose-response relationships are shown in children with behavioral disorders. Exercise duration has a strong linear association with time out of class and self-regulation score. Exercise intensity shows similar, but weaker associations. Children with ADHD may experience the greatest benefits of increases in exercise duration.